The Determinants of Poverty in Mexico: 1996 - Jorge Garza-Rodriguez (ProQuest Dissertations Publishing, 2000)
This study examines the changes in poverty in Mexico for the period 1994-1996 as well as the determinants or correlates of poverty in 1996. The data used in the study come from the National Survey of Income and Expenditures of Households for the years 1994 and 1996. By estimating the Foster-Greer-Thorbecke family of poverty measures, we found that both moderate and extreme poverty increased in Mexico during the 1994-1996 period, and that the depth and severity of poverty also increased. The poverty profiles constructed for both years indicate that poverty incidence is higher for households located in rural areas, for large households, for households where the head has a low level of education, and for households whose head works in a rural or domestic occupation. A logistic regression model was estimated for 1996, with the probability of a household being extremely poor as the dependent variable and a set of economic and demographic variables as the explanatory variables. It was found that the variables that are positively correlated with the probability of being poor are: size of the household, living in a rural area, working in a rural occupation and being a domestic worker. Variables negatively correlated with the probability of being poor are: the education level of the household head, his/her age and whether he or she works in a professional or middle level occupation.
Additional information: Dissertation, University of Missouri, Columbia
Keywords: I32; 360; Poverty; Mexico